Assuring fish demand of India by 2030 through aquaculture development: issues and strategies - Jena, J. K.; Das, P. C. (Indian Farming, 2018)
The need to fulfill the increasing demand of fish as the animal protein source is expected to witness increased fishing pressure on the natural fish stocks and also increased intensification of the existing aquaculture activity. There is a need to have greater focus to harvest more through open-sea farming, which has remained almost unexplored. This should be adequately supported with suitable policies, flow of appropriate technology, increased awareness and infrastructural development across the coasts. Such practice can be an alternate livelihood support for the coastal local communities and can also help in reducing pressure on capture fisheries. Similarly, cautious approach should also be adopted in intensifying the existing aquaculture production systems in both freshwater and brackishwater. Though the current level of utilization of the pond productivity is well below the carrying capacity, there is a need to devise fish farming methods that are more productive, energy efficient, environment friendly, less water consuming, climate resilient and economically efficient. To complement this, there is also a necessity to expand the aquaculture sector horizontally so as to meet the burgeoning fish demand in the future. Considering the present strength of aquaculture sectors, in terms of resource availability, possession of scientific know-how on different aspects of seed production and farming, readiness of the supporting industries for supply of critical inputs, and increased gap between production potential and present production levels, the aquaculture sector in India is not only expected to meet the increasing demand of evergrowing population of the country by 2030, but also likely to boost its export earnings through increased production of high-valued shellfish and finfish species.